MYB1R1 and MYC2 Regulate ω-3 Fatty Acid Desaturase Involved in ABA-Mediated Suberization in the Russet Skin of a Mutant of ‘Dangshansuli’ (Pyrus bretschneideri Rehd.) - Wang, Qi; Liu, Yaping; Wu, Xinyi; Wang, Lindu; Li, Jinchao; Wan, Minchen; Jia, Bin; Ye, Zhenfeng; Liu, Lun; Tang, Xiaomei; Tao, Shutian; Zhu, Liwu; et al. (Frontiers in Plant Science, 2022)
Russeting, a disorder of pear fruit skin, is mainly caused by suberin accumulation on the inner part of the outer epidermal cell layers. ABA was identified as a crucial phytohormone in suberification. Here, we demonstrated that the ABA content in russet pear skin was higher than in green skin. Then, ABA was applied to explore the changes in phenotype and suberin composition coupled with RNA-Seq and metabolomics to investigate the probably regulatory pathway of ABA-mediated suberification. The results showed that ABA treatment increased the expression of ω-3 fatty acid desaturase (FAD) and the content of α-linolenic acid. We identified 17 PbFADs in white pear, and the expression of PbFAD3a was induced by ABA. In addition, the role of PbFAD3a in promoting suberification has been demonstrated by overexpression in Arabidopsis and VIGS assays in the fruitlets. GUS staining indicated that the promoter of PbFAD3a was activated by ABA. Furthermore, MYC2 and MYB1R1 have been shown to bind to the PbFAD3a promoter directly and this was induced by ABA via yeast one-hybrid (Y1H) screening and qRT–PCR. In summary, our study found that ABA induces the expression of MYC2 and MYB1R1 and activates the PbFAD3a promoter, contributing to the formation of russet pear skin. Functional identification of key transcription factors will be the goal of future research. These findings reveal the molecular mechanism of ABA-mediated suberization in the russet skin and provide a good foundation for future studies on the formation of russet skin.